Impact of Weight Regain on Metabolic Disease Risk: A Review of Human Trials - Cynthia M. Kroeger; Kristin K. Hoddy; Krista A. Varady (Hindawi Limited, 2014)
Dietary restriction interventions are effective for weight loss and reduction of chronic disease risk. Unfortunately, most people tend to regain much of this lost weight within one year after intervention. While some studies suggest that minor degrees of weight regain have no effect on metabolic disease risk parameters, other studies demonstrate a complete reversal in metabolic benefits. In light of these conflicting findings, it is of interest to determine how complete weight maintenance versus mild weight regain affects key risk parameters. These findings would have important clinical implications, as they could help identify a weight regain threshold that could preserve the metabolic benefits of weight loss. Accordingly, this review examined the impact of no weight regain versus mild regain on various metabolic disease risk parameters, including plasma lipids, blood pressure, glucose, and insulin concentrations, in adult subjects.